Rebuilding housing along the Mississippi Coast : ideas for ensuring an adequate supply of affordable housing - Bernstein, Mark (Mark A.) (Occasional paper (Rand Corporation), 2006)
In October 2005, RAND Corporation researchers traveled to Mississippi to assist the Governor's Commission on Recovery, Rebuilding, and Renewal and, more specifically, to provide assistance to the Affordable Housing Subcommittee of the Infrastructure Issues Committee. RAND researchers provided support in identifying and developing a list of policy and implementation options that could be useful to local communities in considering how to address affordable-housing issues. In developing this list of options, RAND researchers considered how affordable housing is defined, what affordable-housing issues different U.S. regions face, what the critical challenges are in providing affordable housing, and what strategies are available to deal with those challenges. They investigated how affordable-housing issues have been addressed in the wake of other natural disasters in this country, what lessons have been learned, and what best practices can be taken away from previous natural disaster experiences. They examined the extent and scope of damage to affordable housing that Mississippi sustained, what types of affordable-housing needs that Mississippi might consider addressing during rebuilding, and on what scale. Finally, they studied options available to deal with affordable-housing issues. This report describes affordable-housing issues and myriad rebuilding options.